Human activities recognition of the aged - Neo, Jerryl Kai Wen (Nanyang Technological University, 2023)
This final year project report presents two separate Human Activity Recognition (HAR) systems for monitoring elderly individuals: (1) based on sound and (2) based on smartphone sensors (accelerometer and gyroscope). The sound-based HAR leverages critical sound patterns of everyday activities and objects to detect and recognise human activities and events, while the smartphone Sensor-based system leverages powerful sensors readily available in the modern smartphone for HAR. Both systems are ideal for continuous long-term monitoring of elderly individuals to identify changes in their everyday activities over time.